TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK DIBAWAH UMUR DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Sry Wahyuni, Yulia Risa dan Helfira Citra (Normative Jurnal Ilmiah Hukum, 2017)
This study discusses the Crime of Intercourse against Children under Age Reviewed from Law Number 35 Year 2014. Some fundamental questions are asked to provide direction and focus on this research, namely first, how the judges consideration in deciding criminal cases of intercourse of minors and Second , has the contents of the court verdict sawahlunto reflects a sense of justice related to the decision of intercourse of minors. The study was conducted in Sawahlunto District Court with all its contexts in accordance with the information to be obtained. This research applies a kind of sociological juridical (empirical) research. The data obtained directly from the research site is the District Court Sawahlunto sourced from the existing Criminal Section in court Sawahlunto. In addition, documentation studies are also used to capture relevant data. This study aims to determine know judges' considerations in deciding cases of sexual intercourse against children and knowing the position of the content of the court decision sawahlunto reflects a sense of justice related to the decision of the case of intercourse against minors. The results of the research show that Judging from the above perpetrators' punishment is still less efficient for the perpetrators because the justice awaited by the victims of the family and the whole society is inefficient in their midst, does not mean the severe punishment desired by the public but the punishment according to the deed perpetrators and positive impact for the perpetrators jera.Para law enforcement should be able to look deeply about the rights of children, especially as victims who receive suffering that can not be forgotten. In law enforcement does not mean the perpetrator must be punished with the most severe laws but the appropriate punishment for the perpetrators to be able to cultivate the perpetrators not to repeat his actions in the future. Seeing the contents of the Sawahlunto District Court verdict granted to the defendant the panel of judges ruled prison for 7 (seven) years and a fine of 1 (one) billion rupiah. Still far from being fair to the victims, but compared to the previous cases we have seen and happened, this decision is good enough. It can even be an example of a progressive judge's attitude towards the protection of women's rights.